Cybersecurity Framework for IoT-Integrated Electric Power Information Systems - Mamyrbayev Orken; Berdysheva Dinara Abdumauvlenovna; Zhetpisbayeva Ainur Tursynkanovna; Nurbapa Mekebayev; Tansaule Serikov; Shermantayeva Zhazira; Kydyrbekova Aizat (International Journal of Industrial Engineering and Management)
The integration of Internet of Things (IoT) devices in electric power information systems has introduced unprecedented cybersecurity challenges. This study develops and evaluates a comprehensive cybersecurity framework tailored for IoT-integrated power grids, addressing the unique vulnerabilities and complexities of these critical systems. A multi-layered security approach was designed, incorporating device authentication, encrypted communication, and machine learning-based anomaly detection. The framework underwent extensive testing across six distinct attack types (unauthorized access, man-in-the-middle, DDoS, malicious command injection, firmware tampering, and data exfiltration), with over 10,000 simulated attack scenarios conducted in a testbed environment mimicking a regional power grid with up to 10,000 IoT devices. The framework demonstrated high effectiveness, with average threat detection rates of 97.9% and prevention rates of 97.1% across all attack vectors. Performance testing revealed sub-linear CPU utilization growth as IoT devices scaled from 100 to 10,000, with only a 2.3% increase in network latency at the 1,000-device scale. The system maintained 98.7-99.8% availability during attacks and achieved 94-98% compliance with key industry standards. These findings demonstrate the framework's robust capabilities in securing IoT-integrated power systems while highlighting areas for future research in extreme scalability scenarios and real-world implementation challenges.